Comparative study on the effects of different animal manure on the growth of green onions. - Villa, Jeseryl S. (1992.)
A comparative study on the effects of different animal manure namely, guano and swine on the growth of native onions was conducted. Observation showed that the guano gave the highest results in all parameters, which include number of tillers, size of bulb and fresh weight yield. It was followed by the swine manure and then the control, which gave the lowest results. Statistical analysis using ANOVA and DMRT at 0.05 level of significance revealed, that the difference among the treatments in all parameters were significant. Thus, application of animal manures especially guano can improve the growth of native onions as compared to ordinary unfertilized oil.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Onions, Green